Description of a new species of Parotocinclus (Siluriformes, Hypoptopomatinae) from the rio Tapajos basin - Roxo, Fabio F. [UNESP]; Silva, Gabriel S. C. [UNESP]; Oliveira, Claudio [UNESP] (Pensoft Publ, 2016)
A new species of Parotocinclus is described from three small tributaries of the rio Tapajos basin, Mato Grosso State, Brazil. The new species can be distinguished from its congeners by presenting the following characters: (1) a triangular dark blotch at the anterior base of the dorsal fin, (2) the absence of an adipose fin but presence of one small platelet at typical adipose-fin region, (3) the abdomen completely covered by dermal plates, (4) a pectoral girdle totally exposed, (5) a single series of bicuspid teeth, and (6) the higher number of bicuspid premaxillary and dentary teeth.
Keywords: Biodiversity; Cascudinhos; freshwater; Neotropical fish; taxonomy